79.4k views
2 votes
4. Graph the inequality:
y \ \textless \ x ^2 + 2x - 3

User Or Cohen
by
5.8k points

1 Answer

6 votes

Step-by-step explanation:

First, we need to graph the equality y = x² + 2x - 3

So, to graph the parabola, we need to identify the vertex and 2 points in the parabola.

The vertex can be calculated as:


x=-(b)/(2a)=-(2)/(2(1))=-1

Where b is the number beside the x and a is the number beside the x². Then the value of y is equal to:


\begin{gathered} y=x^2+2x-3 \\ y=(-1)^2+2(-1)-3 \\ y=1-2-3 \\ y=-4 \end{gathered}

So, the vertex (- 1, - 4)

Then, to find 2 points in the parabola we can replace x by 0 and x by -2 as:

For x = 0


\begin{gathered} y=x^2+2x-3 \\ y=0^2+2\cdot0-3 \\ y=-3 \end{gathered}

For x = -2


\begin{gathered} y=(-2)^2+2\cdot(-2)-3 \\ y=4-4-3=-3 \end{gathered}

Therefore, we have the vertex (-1, -4) and the points (0, -3) and (-2, -3)

Then, the inequality is y less or equal than the parabola so, the zone for the inequality is:

So, the graph of the inequality is the region below the graph of the parabola.

4. Graph the inequality: y \ \textless \ x ^2 + 2x - 3-example-1
User Tamora
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.